Effectiveness of Mendong (Fimbristylis globulosa) as A Phytoremediation Agent for Total Ammonia and Total Nitrogen Leachate - Anwar, Labib; Ulfah, Maria; Kaswinarni, Fibria (Journal of Environmental and Science Education, 2025)
Landfills are one of the causes of environmental pollution resulting from the disposal of human activity waste without further treatment (Yusri et al., 2020). In 2023, the total waste generation reached 1,270.00 tons per day, with 900 tons of waste being transported to the landfill each day (Harjanti, 2020). This waste accumulation produces leachate—a thick, dark-colored liquid that carries pollutants and materials from the waste—which has the potential to contaminate the surrounding environment, including the Kreo River. Therefore, phytoremediation using Mendong plants is proposed to reduce the pollutants in the leachate. This research employed an experimental method with a Completely Randomized Design (CRD), using Mendong plants (Fimbristylis globulosa) and three biomass variations: P0 (0 g), P1 (1000 g), and P2 (2000 g). Each treatment involved 10 liters of leachate and was replicated three times. The phytoremediation process proved effective in reducing total ammonia levels in the leachate, with a reduction of up to 63%, and the highest total nitrogen reduction reached 53%. This phytoremediation approach can assist in reducing excess total ammonia in water bodies by absorbing organic pollutants through plant roots, as Mendong exhibits hyperaccumulator and hypertolerant properties. It is concluded that Mendong plants are effective in lowering total ammonia and total nitrogen levels in landfill leachate.